Mercury removal by thiol‐functionalized metal oxide–carbon black sorbent and mixed‐matrix membranes. Issue 3 (24th September 2012) - Meeks, Noah D.; Davis, Erica; Jain, Mohit; Skandan, Ganesh; Bhattacharyya, D.
<x xml:space="preserve">Abstract</x> Aqueous mercury sorption is achieved using a novel thiol‐functionalized metal oxide‐coated carbon sorbent. The material is hydrolytically and thermally stable (up to 250°C) because of the formation of covalent siloxane bonds on functionalization and increased hydrophobicity. The particles were synthesized with a variety of morphologies; the base particles are ∼80 nm and a nonuniform metal oxide (including silica) coating less than 5 nm thick. This sorbent material has a high equilibrium capacity for mercury (∼60 mg/g) at concentrations up to ∼150 mg/L. The Langmuir constant for equilibrium sorption (ka/kd) is K = 16.9 L/mol. Packed column experiments using real water reduced mercury levels to below detectable limits. Mixed‐matrix membranes (sorbent particles and polysulfone) were synthesized to combine the ease of surface functionalization on particles with advantages of polymer membranes. Membranes with up to 50 wt % particles were synthesized, with sorption capacities at 200 mg/g sorbent or greater due to dispersion of particles in the matrix and the use of small particles, which are impractical in packed column operations. A regeneration scheme is proposed using multifunctional particles (thiol and sulfonate moieties). Initial experiments showed that mild regeneration conditions (dilute HCl at pH 4) partially regenerated the sorbent particles. © 2012 American Institute of Chemical Engineers Environ Prog, 32: 705–714, 2013